Analysis of the Impact of Investment Attractiveness on The Socio-Economic Development of the Bustan District of the Andijan Region (European Journal of Economics, Finance and Business Development, 2023)
The article discusses the role and importance of the attractiveness of the investment environment in the socio-economic development of the regions of our republic, the existing problems, analytical data, conclusions, suggestions and recommendations in this regard.